Physiological and technical commitment during a 300-m in-line skating trial in athletes of different age categories - Invernizzi, P. L.; Scurati, R.; Crotti, M.; Bosio, A.; Longo, S.; Esposito, F. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: This study investigated the differences in strength, technique and time performance in in-line skaters of three age categories during a 300-meter trial. Possible correlations among these variables were also assessed. METHODS: Thirty-six elite in-line skaters (Cadets, Juniors and Seniors, N.=12 each; 14±1, 16±1, and 24±6 years of age, respectively) performed a 300-m trial on an outdoor oval track. Total time (Ttot), 100-m fractions and duration of each skating technique (initial acceleration phase, straight push and cross-over) were recorded. A squat jump (SJ) was performed before and after the trial. Heart rate, blood lactate concentration ([La-]) and rate of perceived exertion (RPE) were collected before, during and at the end of the trial. RESULTS: Ttot was longer and SJ lower in Cadets compared to the other groups. Seniors employed the cross-over technique for a longer period than the straight push technique, compared to Juniors and Cadets. Ttot correlated negatively with SJ in Seniors. The number of significant correlations between skating techniques` duration and both Ttot and SJ increased with age category. No differences among groups were found for heart rate, [La-] and RPE. CONCLUSIONS: With increasing age category, leg strength appeared to be the more related aspect to skating performance. To improve 300-m in-line skating performance, trainers should pay particular attention to the enhancement of leg strength and cross-over skating technique.